Developing a Culturally Nuanced Assessment Tool for Workforce Diversity Management in Nigerian Higher Education: A Framework for Enhancing Institutional Performance and Inclusion - Asabor, Mary Bivwiere; Alordiah, Caroline (NIU Journal of Educational Research; Vol 11 No 2 (2025): NIU Journal of Educational Research, Vol. 11, No. 2, June 2025DO - 10.58709/niujed.v11i2.2237, 2025)
Workforce diversity is widely acknowledged as a vital element affecting the performance and sustainability of higher education institutions. This study examines the development of a measurement instrument to assess the success of diversity management in Nigerian universities, highlighting the necessity for a standardised, culturally relevant evaluation tool. Variety in global higher education institutions is associated with enhanced innovation, academic achievement, and organisational efficiency; yet, managing this variety is a difficulty, especially within the Nigerian setting. The study identifies deficiencies in diversity management, emphasising the lack of established instruments to evaluate institutional strategies for workforce diversity. It presents a conceptual framework that incorporates essential characteristics such as leadership commitment, inclusive recruitment techniques, organisational culture, and diversity policies. The study seeks to create an instrument that functions as a practical tool for institutional evaluation and a resource for improving diversity policies and practices by integrating social identity theory, institutional theory, and the resource-based view. The results are anticipated to enhance the literature on diversity in African higher education, offering insights into how Nigerian universities can cultivate inclusive cultures that advance academic achievement and institutional performance. Keywords: workforce diversity, higher education, diversity management, Nigerian universities, inclusion, assessment tool, institutional performance, cultural competence, leadership, organizational culture